Vamos brincar de roda ? movimentando-se e aprendendo música - Almeida, Eliene Nunes de (2023)
The purpose of this research was to carry out a musical creative process with the students of the 1st year of the Hidelbrando Silva Municipal School – Cabedelo. Our objective was to relate the practice and learning of music teaching to the body experience. In this way, the research in question worked with music contents inspired by Dalcroze's methods, making a reassessment, considering the contemporaneity and the socio-political-cultural reality of the group to be researched. We used the songs of nursery rhymes for the dynamics of the classes/workshops and raised a discussion about its origin, the role it has been playing, and the function it is assigned today, and the didactic possibilities. In this sense, 10 classes/workshops were held in person, lasting 45 minutes, with the only class of the 1st year of elementary school, with all 14 students enrolled in this year/series aged between 5 and 7 years. For each class, we use a different musical song, followed by a proposal, objective and different skills to be worked on. The activities were carried out collectively, to awaken the feeling of belonging in the group, as well as guaranteeing the interaction of all, always using the songs from the children's songbook and emphasizing the music and the body in movement, using playfulness and creation. This research is participatory and the methodology is applied in nature because it was consolidated through observations of experiences at school. The object of study was the descriptive research, where the data of the 10 proposals of classes that we organized for the 1st year class chosen for the application were observed. The approach was qualitative, because in its conclusion, the entire process was analyzed and reported. As a result, we obtained the elaboration of 10 curricular proposals along with the lesson plans, for the teaching of music for the first grade of elementary school, using the nursery rhymes, and the body in motion. We also produced a video/documentary of the classes/workshops experiment in order to share the acquired knowledge.